Concordance between the tuberculin skin test and interferon gamma release assay (IGRA) for diagnosing latent tuberculosis infection in patients with systemic lupus erythematosus and patient characteristics associated with an indeterminate IGRA. (October 2016) - Cho, H; Kim, Y W; Suh, C-H; Jung, J-Y; Um, Y-J; Jung, J-H; Kim, H-A
Objective: We investigated the agreement between the tuberculin skin test (TST) and the QuantiFERON-TB gold (QFT-G) assay in the diagnosis of latent tuberculosis infection (LTBI) in patients with systemic lupus erythematosus (SLE). Furthermore, we evaluated the factors associated with indeterminate results in the QFT-G assay in patients with SLE. Methods: We enrolled 136 patients with SLE prospectively, and compared them to 66 patients with rheumatoid arthritis (RA). In addition to the TST, QFT-G assay, patients' medications, and Bacillus Calmette-Guérin (BCG) vaccination status were also investigated. A positive TST or QFT-G assay result without an active tuberculosis lesion on chest x-ray was considered to indicate a diagnosis of LTBI. Results: The prevalence of LTBI was 26.5% in patients with SLE and 30.3% in patients with RA. The agreement between the TST and QFT-G assay was fair in SLE patients, but poor in RA patients. BCG vaccination was one factor associated with discordance between TST and QFT-G. Older age and higher SLE Disease Activity Index (SLEDAI) score were associated with a negative TST/positive QFT-G result in patients with SLE. Higher SLEDAI score and increased glucocorticoid dose were associated with an indeterminate result in the QFT-G assay for patients with SLE. Conclusions: Agreement between the QFT-G assay and TST in patients with SLE was found to be fair. However, BCG vaccination status, age, and SLEDAI score are all factors that could result in discordance between the two tests. Indeterminate results from the QFT-G assay may be caused by a higher SLEDAI score or increased glucocorticoid dose.